ALIGNING NUTRITION KNOWLEDGE AND DIETARY HABITS OF GENERATION Z-IS THERE A ROOM FOR IMPROVEMENT? - Halasi, Szabolcs; Djordjević, Miljana; Kiss, Ferenc; Šoronja-Simović, Dragana; Maravić, Nikola; Horvat, Olga; Šaranović, Žana (Food and Feed Research, 2021)
The potential association between determinants such as nutrition knowledge and dietary habits with obesity development among adolescents of generation Z (Zoomers) was investigated in the presented study. Data regarding meals consumption frequency, snack choice and familiarity with amounts of basic food nutrients in diet were gathered throughout a self-designed questionnaire from 854 adolescents (11‒18 years) attending elementary and secondary schools in the Autonomous Province of Vojvodina, Serbia. The corresponding data was analysed and discussed primarily concerning BMI-for-age, and subsequently, gender and educational stage. The association between BMI categories and examined determinants was tested using chi-square and multinomial logistic regression statistics. Although most of the surveyed adolescents had normal weight (72.1%), a notable share of overweight adolescents was also detected (17.9%). Additionally, observed irregularities in breakfast and dinner consumption frequencies and participants’ modest nutrition knowledge can contribute to further diet deterioration. Statistically significant but weak associations between BMI-for-age and choice of snack, dinner consumption frequency, as well as the frequency of salty snack and fast food consumption, were noted. Furthermore, an increase in nutrition knowledge was inversely associated with obesity prevalence (OR 6.56, 95% CI 1.388‒31.037).As an outcome, the need for improvement regarding studied determinants especially nutrition knowledge is established and represents a task to achieve through health promotion strategies among generation Z.
Keywords: Zoomers; nutrition knowledge; body mass index; meal habits; obesity